Metropolitan construction carbon emission efficiency: an integrative static-dynamic analytical framework - Jianing Hu; Wanxiang Yao; Gangwei Cai; Qinfeng Zhao; Chanjuan Wang; Tongyu Xu; Chunyan Shi; Weijun Gao (Environmental Research Communications)
Taking urgent action to combat climate change and promote sustainable cities are part of the 17 Sustainable Development Goals, which demand immediate action from all countries. Enhancing the carbon emission efficiency of the construction industry (CICEE) from the ‘static-dynamic’ perspective is crucial in addressing climate change. This study utilized the super slack-based measure model to analyze static efficiency. The Malmquist-Luenberger index model, multiple non-linear regression model, and principal component analysis were used to research the driving factors dynamically. Factors included technical change (TC), pure technical efficiency change (PEC), and scale efficiency change (SEC), which were subdivided into 21 variables. The panel data was from 11 cities in Zhejiang from 2007 to 2019. The results indicated that while static carbon efficiency values were generally effective, more than half of the cities experienced a significant decline in carbon efficiency in 2019, with an average decrease of 52%. Efficiency levels were higher in northern Zhejiang and lower in the southeastern region. CICEE values over one were primarily attributed to high TC levels and stable PEC and SEC conditions. Additionally, a generalized framework for improving CICEE was constructed, assisting policymakers in identifying reasons for low CICEE and providing targeted strategies to reduce emissions and increase efficiency.